In Vitro Mucolytic Activity of Cardamom Fruit (Amomum compactum) Decoction on Duck Egg Albumens - Vitri, Desy Aryanti Pardilla; Aini, Siti Rahmatul; Saputri, Legis Ocktaviana (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Cardamom (Amomum compactum) is empirically used as a cough medicine by using its seeds and fruits. Cardamom seeds have been shown to have mucolytic activity at a concentration of 0.8%, while cardamom fruit has not been studied. This study aimed to determine the mucolytic activity of cardamom fruit decoction at variation concentrations. Mucolytic activity tests were carried out in vitro on duck egg albumens at 3%, 6%, and 12% variation concentrations of cardamom fruit decoction. N-acetylcysteine 0.1% was positive control, while phosphate buffer and Tween 80 were negative controls. The mucolytic activity was determined based on the viscosity value measured by flow time using an Ostwald viscometer and density measurement using a pycnometer. Data from each group were analyzed using SPSS with parametric One-Way ANOVA and Post Hoc tests. The results showed that cardamom fruit decoction at concentrations of 3%, 6%, and 12% had values that were not significantly different from N-acetylcysteine (p>0.05) and there was no significant difference (p>0.05) between each concentration group. Accordingly, the research concludes that cardamom fruit decoction at concentrations of 3%, 6%, and 12% has mucolytic activity comparable to N-acetylcysteine.